How Much Voice for Borrowers? Restricted Feedback and Recursivity in Microfinance. Issue 4 (11th September 2017) - Mader, Philip
Abstract: This paper studies the governance of microfinance and asks about its recursivity: whether the system is responsive to changes prompted by feedback from borrowers or not. It draws on Hirschmann's heuristic of exit and voice and the idea of participation in development, to examine three channels of feedback from borrowers to rule‐makers and ask to what extent they have facilitated or restricted recursivity in microfinance. The standardisation of microfinance along a financial template is shown to have created very open flows of financial information, useful for monitoring clients' exit, but not granting them voice. The more recent creation of systems for social performance management and pursuing 'responsible' microfinance, however, has not resulted in similarly robust information flows, because, despite intentions to capture client satisfaction and feedback, these channels are severely restricted. They offer borrowers little chance to practically exercise voice and convey feedback which affects the rules. Recursivity studies, it is suggested, might integrate participation and exit/voice frameworks to explore the prospects of feedback from grassroots rule‐subjects and better understand the factors that can restrict it. For microfinance, it is suggested that government regulation and clients' collective action could be necessary where the sector's governance system shows itself to be unresponsive. Abstract : With potential harm to borrowers being a real concern, independent watchdogs and grassroots associations to represent debtor interests would appear to hold more promise for giving clients voice than proceeding further with industry self‐regulation.